At søge indsigt på tværs: Hvordan og hvorfor sammenligne forskelligartede professionsfelter? - Pedersen, Inge Kryger; Blok, Anders; Meilvang, Marie Leth (Tidsskrift for Professionsstudier, 2020)
This article argues that qualitative comparative research would benefit from abductive inferences to freeing the practice of comparison from its too-restrictive theory. Challenging some of more traditional and abstract images of how to do comparison within the sociology of professions, we in an ongoing research project engage in an inferential process aimed at conceptual development while seeking to hinder a separation between empirical practices and academic analyses. To demonstrate our methodological considerations, we turn to our research project on professions about professional work changes within three professional proto-jurisdictions of water-related climate adaptation, innovation management, and prevention of lifestyle-related diseases.